Revision of three taxa of Ophiorrhiza (Rubiaceae) from China - Wu, Lei; Liu, Wen-Jian; Nguyen, Khang Sinh (Phytotaxa, 2019)
Through field observations, recollections at known sites and research on specimens and relevant literature, Ophiorrhiza alatiflora H.S.Lo is re-instated; O. alatiflora H.S.Lo var. trichoneura H.S.Lo and O. aureolina H.S.Lo f. qiongyaensis H.S.Lo are reduced to the synonym of O. baviensis Drake and O. subpunicea Craib, respectively. The lectotype of Ophiorrhiza baviensis is here designated. In addition, the detailed description, colour photographs and conservation status of the three species are provided here.